Effect of Characteristics of Ground Motion on Seismically Induced Sliding Surface of Slopes - Muhammad Irslan Khalid (Applied Sciences, 2021)
The seismic performance of slopes is typically evaluated with a pseudo-static method using equivalent horizontal load or with Newmark sliding block analysis. In both procedures, the definition of the potential sliding surface is a required input. The sliding surface has been reported to be marginally influenced by the input ground motion and, therefore, is most often assumed from a pseudo-static procedure. In this study, extensive series of two-dimensional dynamic nonlinear finite element analyses are performed to evaluate the sensitivity of the sliding surface on the slope geometry, soil strength parameters, and input ground motion characteristics. It is demonstrated that the sliding surface may vary with the intensity and frequency characteristics of the input motion. Slopes with inclination angle equal or less than 35° are shown to be marginally influenced by motion intensity if the mean period (Tm) < 0.3 s. However, slopes inclined at 45° are revealed to be more sensitive to the motion intensity and Tm. For motions with Tm > 0.3 s, the sliding surface is demonstrated to widen with an increase in the intensity of the input ground motions. The degree of widening increases proportionally with an increase in Tm. It is, therefore, recommended to derive sliding surfaces from a dynamic analysis for steep slopes.